Meaningful assessment of learners' understandings about scientific inquiry-The views about scientific inquiry (VASI) questionnaire - Lederman, Judith S.; Lederman, Norman G.; Bartos, Stephen A.; Bartels, Selina L.; Meyer, Allison Antink; Schwartz, Renee S. (Journal of research in science teaching, 2014)
Helping students develop informed views about scientific inquiry (SI) has been and continues to be a goal of K‐12 science education, as evidenced in various reform documents. Nevertheless, research focusing on understandings of SI has taken a perceptible backseat to that which focuses on the “doing” of inquiry. We contend that this is partially a function of the typical conflation of scientific inquiry with nature of science (NOS), and is also attributable to the lack of a readily accessible instrument to provide a meaningful assessment of learners' views of SI. This article (a) outlines the framework of scientific inquiry that undergirds the Views About Scientific Inquiry (VASI) questionnaire; (b) describes the development of the VASI, in part derived from the Views of Scientific Inquiry (VOSI) questionnaire; (c) presents evidence for the validity and reliability of the VASI; (d) discusses the use of the VASI and associated interviews to elucidate views of the specific aspects of SI that it attempts to assess; and (e) discusses the utility of the resulting rich‐descriptive views of SI that the VASI provides for informing both further research efforts and classroom practice. The trend in recent reform documents, unfortunately, ignores much of the research on NOS and SI and implicitly presumes that the “doing” of inquiry is sufficient for developing understandings of SI. The VASI serves as a tool in further discrediting this contention and provides both the classroom teacher and the researcher a more powerful means for assessing learners' conceptions about essential aspects of SI, consonant with the vision set forth in the recently released Next Generation Science Standards (Achieve, Inc., 2013). © 2013 Wiley Periodicals, Inc. J Res Sci Teach 51: 65–83, 2014